The age of innocence - Wharton, Edith, 1862-1937.; Orgel, Stephen (Oxford ; New York : Oxford University Press, 2006)
Edith Wharton's most famous novel, written immediately after the end of the First World War, is a brilliantly realized anatomy of New York society in the 1870s. The charming Newland Archer is content to live within its constraints until he meets Ellen Olenska, whose arrival threatens his impending marriage as well as his comfortable future. - ;'They lived in a kind of hieroglyphic world, where the real thing was never said or done or even thought, but only represented by a set of arbitrary signs.'. Edith Wharton's most famous novel, written immediately after the end of the First World War, is.
Contents; Acknowledgements; Introduction; Note on the Text; Select Bibliography; A Chronology of Edith Wharton; THE AGE OF INNOCENCE; Explanatory Notes.
Includes bibliographical references (pages xxi-xxii).
Print version record.
eBooks on EBSCOhost
Keywords: Upper class -- New York (State) -- New York -- Fiction; Marriage -- Fiction; New York (N.Y.) -- Social life and customs -- 19th century -- Fiction; Classes supérieures -- New York (État) -- New York -- Romans, nouvelles, etc; Mariage -- Romans, nouvelles, etc; FICTION; Romance; LITERARY CRITICISM; Manners and customs; Marriage; Upper class; New York (State) -- New York; 1800-1899; Electronic books; Fiction